Communication competence of undergraduate healthcare students in Thailand: A cross-sectional study - Chaiyaphum, Nattapong; Woranuch, Supansa; Khant, Aung Min (Lentera Perawat, 2026)
Background: Effective communication is a cornerstone of patient-centered healthcare, directly influencing treatment adherence, patient satisfaction, and safety outcomes. In Thailand, where cultural diversity and family involvement play vital roles in healthcare, inadequate communication remains a persistent challenge affecting patient well-being. Strengthening communication competence among undergraduate healthcare students is crucial for preparing future professionals to deliver safe, empathetic, and culturally sensitive care. Objective: This study aimed to assess the communication competence of undergraduate healthcare students in Thailand and to examine whether demographic factors influence these skills. Methods: A cross-sectional quantitative design was employed. Data were collected from 212 undergraduate healthcare students enrolled in medicine, nursing, pharmacy, dentistry, and allied health programs at three major public universities in Thailand. The validated Self-Efficacy 12 (SE-12) questionnaire was used to measure students’ self-perceived communication competence. Data were analyzed using descriptive statistics and chi-square tests to identify associations between communication competence and demographic characteristics. Results: Among respondents, 55.2% demonstrated good communication competence, while 44.8% exhibited poor competence. No statistically significant associations were found between communication competence and gender, age, year of study, or faculty affiliation (p > 0.05). These findings suggest that sociodemographic characteristics do not significantly influence communication abilities among healthcare students. Conclusion: Nearly half of Thailand’s undergraduate healthcare students demonstrated limited communication competence, highlighting a critical need for targeted educational interventions. Integrating structured, experiential, and culturally grounded communication training into healthcare curricula is essential to enhance competence, improve patient safety, and promote high-quality, patient-centered care.